Career and financial situation of patients diagnosed with soft tissue sarcomas - Laros, Nele; Sungu-Winkler, Kiangenda Trésor; Gutermuth, Susanne; Wartenberg, Markus; Hohenberger, Peter; Seifart, Ulf; Kasper, Bernd (Oncology research and treatment, 2020)
Background: After receiving a cancer diagnosis patients face many challenges. The association between career situation and financial problems caused by cancer has a substantial impact on quality of life (QoL) among cancer patients. Indeed, the QoL such as physical and mental health of cancer patients is lower when the risk of psychological disorders or distress increases, and chances for cancer cure are reduced. Progress in therapeutic intervention allows many cancer patients a social reintegration into their careers. About one third of cancer patients are younger than 65 years, and with the constant increase in work life periods, a cancer diagnosis also presents a financial burden for those affected. Objectives: The main objective of this study was to analyse the social QoL in the context of factors related to career and financial situation among patients diagnosed with soft tissue sarcomas (STS). Methods: A descriptive non-experimental research design was used to conduct a cross-sectional survey over a period of 6 months, between May and November 2016, in collaboration with the Sarcoma Unit at the Mannheim University Medical Centre, Mannheim, Germany, the patient organisation “Das Lebenshaus e.V.,” and the German Pension Insurance Hessen (Deutsche Ren-tenversicherung: DRV Hessen)/Pension Fund. We analysed data of 30 patients diagnosed with STS using self-outcome questionnaires in combination with retirement insurance data from the date of first diagnosis up to 3 years afterwards. Out of 280 questionnaires, we received 86 completed forms, of which 56 were excluded. The remaining questionnaires of 30 patients were analysed according to self-determined outcomes and included a calculation of the financial changes caused by the disease. Only patients covered by pension insurance were included in the study. Results: Thirty patients (24 women) whose median age at first diagnosis was 48.7 years (range 31-61 years) were included in the analysis. The average unemployment rate was 8.8 months, and for 67% (20 patients) the employment situation changed after the period of unemployment. Eight patients requested a retirement pension (reduced income insurance), 4 patients reduced their weekly working hours, and 3 patients lost their jobs due to complications of the disease. The data analysis revealed that, among these patients, one benefited from an income increase of about 24%, another one received a regular old-age pension, and 4 patients reported reduced income for other reasons. In total, mean income has been reduced by 26%. Considering only the 8 patients who applied for a pension, partial or total unemployment benefits resulted in an average loss of income of up to 62%. Conclusions: Reduced ability to work may cause severe financial problems for those affected by the diagnosis of STS. We found an average income reduction of 26%, for those requesting pension payments of 62%. This eventually relates to a higher risk of reduced wealth and may lower the patients’ social standing.
Online publiziert: September 16, 2020
Gesehen am 04.08.2025